(untitled) (Proceedings of the Mongolian Academy of Sciences, 2019)
This work shows some of the results of investigation into pseudo total content of heavy metals in the surface soil of Ulaanbaatar. The main objectives of this study are to (i) evaluate temporal variability of pseudo-total content of Pb, Cu, Zn, Cd, Cr, Ni, Co and Mn in surface soil of Ulaanbaatar collected from 2003 to 2018, (ii) identify the main discriminates - metals during the years 2003-2018 years and, (iii) investigate the interdependence of main discriminates on the soil reaction (pH) and soil organic matter. Due to urbanization and negative human activities, surface soil in Ulaanbaatar losing their natural features, which are changing, while the spatial and temporal distribution of heavy metals in urban surface soil is becoming irregular. In Ulaanbaatar surface soil, the mean concentration of Cu, Zn and Pb much mois very high and the mean concentration of Co is lower than background soil. In some land use zones, it was found that the mean concentraion of Zn and Cr was considerably higher than the permissible level. The pollution condition of Mn, Zn, Cr, Ni and Cd was the same in 2010-2018 and the pollution conditions of Pb, Cu and Co are different. The main discriminants are Pb, Cu and Co. In Ulaanbaatar soil, a strikingly close correlationhip was established for Cu, Pb with the soil organic matter, and for Cd, Zn, Cr with the pH, respectively.